Implementation of service-based e-government and establishment of state IT components interoperability at local authorities - Pappel, Ingrid; Pappel, Ingmar (2011 3rd International Conference on Advanced Computer Control, 2011)
This paper addresses different institutional and technological contexts, which must be considered when implementing e-government features at local authorities. Estonian success in establishment of nation-wide digital record management is based on broad use of various centralized IT solutions (X-road, DEC etc.) and provision of interoperability of those solutions. Initial prerequisite for efficient paperless and record management is a well-implemented and well-operating electronic record management system that constitutes the main process layer of a local authority. This paper is based on e-governance project1 which has enabled to provide facilities for paperless management in about 100 local authorities. The paper concludes with a discussion of the advantages of service-based orientation for this project, and based on this, recommendations for similar projects with an infrastructural component undertaken by local governments.